2008
DOI: 10.1051/0004-6361:200810543
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic rays and the magnetic field in the nearby starburst galaxy NGC 253

Abstract: Context. Nearby edge-on galaxies showing a synchrotron halo are nearly ideal objects for studying the transport of cosmic rays (CRs) in galaxies. Among them, the nearby starburst galaxy NGC 253 hosts a galactic wind indicated by various ISM phases in its halo. Aims. The diffusive and convective CR transport from the disk into the halo is investigated using the local CR bulk speed. The connection between the CR transport and the galactic wind is outlined. Methods. We observed NGC 253 with the VLA at λ6.2 cm in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
179
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 135 publications
(191 citation statements)
references
References 31 publications
9
179
2
1
Order By: Relevance
“…It is apparent that the bulk speeds of the wind, driven by the vertical gradient of CR pressure, reach 65 ± 15 km s −1 at z = 2 kpc. Vertical systematic winds of bulk speeds, comparable to rotational galactic velocities, influence large-scale structures of galactic magnetic fields and are observed in external starburst galaxies such as NGC 253 (see Heesen et al 2007Heesen et al , 2009.…”
Section: Resultsmentioning
confidence: 99%
“…It is apparent that the bulk speeds of the wind, driven by the vertical gradient of CR pressure, reach 65 ± 15 km s −1 at z = 2 kpc. Vertical systematic winds of bulk speeds, comparable to rotational galactic velocities, influence large-scale structures of galactic magnetic fields and are observed in external starburst galaxies such as NGC 253 (see Heesen et al 2007Heesen et al , 2009.…”
Section: Resultsmentioning
confidence: 99%
“…If CRE diffusivity is much lower A123, page 12 of 14 in the z direction, then a wind could possibly exist. It has been shown observationally (Dahlem et al 1995;Heesen et al 2009) that the diffusion coefficient in the z direction is several times lower than the radial component. Heesen et al (2016), using 1D cosmic ray electron transport models and Australia Telescope Compact Array observations of two edge-on galaxies, found that the cosmic ray transport in the halo of NGC 7090 is advection dominated with a velocity of approximately 150 km s −1 , while NGC 7462 is diffusion dominated with a diffusion coefficient of D = 3.0 × 10 28 E 0.5…”
Section: Discussionmentioning
confidence: 99%
“…Not only do relativistic electrons leave via diffusion but in starburst galaxies, large-scale galactic winds can also advect CREs out of the disk into the halo on a shorter timescale than the diffusion observed in M 82 (Adebahr et al 2013) and NGC 253 (Heesen et al 2009). There is no observational evidence for a global outflow or a galactic-scale wind in M 51 (Mao et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We recall that a straightforward estimate of the wind velocity is ≥150 km −1 (Heesen et al 2009a), but this flow is associated with only a small part of the interstellar medium. In contrast, conventional mean-field galactic dynamos deal with an averaged wind velocity u.…”
Section: Discussionmentioning
confidence: 99%
“…The key ingredient of the model is the galactic wind which is traced by the cosmic-ray bulk flow, which is as large as u = 300 ± 30 km s −1 (Heesen et al 2009a). Heesen et al argue that the cosmic-ray bulk flow is the sum of the wind velocity of the gas and Alfvén velocity, which may reduce the estimate by up to 150 km s −1 .…”
Section: The Galactic Modelmentioning
confidence: 99%